PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH TUTUP BOTOL PLASTIK MENJADI AKSESORIS GANTUNGAN KUNCI UNTUK MENINGKATKAN NILAI JUAL DAN DAYA SAING DI DESA SUKODONO SIDOARJO - Yuliyah Risma Wati; Budi Arjo Lakmono; Indriasari Martha Susilo; Ferdinan Billah Utomo; Rega Lestari Putri Dayana; Suparti; Milawati; Pismia Sylvi; Tiara Sevi Nurmanita; Muhammad Yusron Maulana El-Yunusi (AlMurtado Journal of Social Innovation and Community Service, 2026)
Plastic waste remains a serious environmental issue in Indonesia due to high plastic consumption and low waste management rates. One type of plastic waste commonly found in communities is bottle cap waste, which is often underutilized. This condition also occurs in Sukodono Village, Sidoarjo Regency, where household waste management is generally limited to disposal without recycling efforts. This community empowerment program aimed to improve community skills in transforming plastic bottle caps into keychain accessories with economic value and market competitiveness. The program applied the Participatory Action Research (PAR) method by actively involving the community in planning, implementation, and evaluation processes. The activities included socialization, production training, packaging, branding, and product marketing trials through digital platforms such as Shopee. The results showed that participants were able to understand and practice the recycling process into creative products with economic value. The program also increased environmental awareness and contributed to reducing plastic waste in the village environment.